EARLY DETECTION AND PREVENTION METHODS OF ADVERSE DRUG REACTIONS IN MEDICAL PRACTICE - O`ktamova N.B; Boymuratov F.T (ILMIY YANGILIKLAR VA INTELLEKTUAL TADQIQOTLAR, 2025)
Abstract: Adverse drug reactions (ADRs) remain a significant global healthcare concern, contributing to increased morbidity, mortality, and healthcare costs. Early detection and prevention of ADRs are essential to ensure patient safety and improve therapeutic outcomes. Identifying risk factors such as polypharmacy, comorbidities, age-related changes in pharmacokinetics, and genetic predispositions allows clinicians to tailor pharmacotherapy to individual patients. The implementation of pharmacovigilance systems, routine monitoring, patient education, and electronic drug-interaction databases significantly reduces the occurrence of preventable adverse reactions. This article reviews modern strategies for early recognition, monitoring, and prevention of ADRs in clinical practice and emphasizes the role of multidisciplinary collaboration in achieving safe and effective medication use.